The activity of Physical Education Trainee Teachers across emotionally significant situations experienced on school placement - Descoeudres, Magali (Swiss Journal of Educational Research, 2023)
This study aims to understand the development of PE trainee teachers based on emotionally significant situations. The first part aims to draw a topography of emotionally significant situations from 139 PE trainee teachers. The second part, clinical, with five trainee teachers, aims to understand how emotionally significant situations hinder or enhance their activity’s development. The results show that PE trainee teachers experience emotionally significant situations which promote a development through the control of new operations. These results open up possibilities for current dual education systems, particularly by taking into account the subjective dimension of the profession.